2021
DOI: 10.1080/24759651.2021.1875615
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsions based edible coatings with potential food applications

Abstract: With the advancement in the technologies and globalization, people are now focusing more on healthy products such as fruits, vegetables having good nutrition capability with enhanced shelf life. The edible coating is one such technique that can be used to enhance the shelf life of fruits, vegetables, and other food products. Various types of edible coatings such as protein based, lipid based, pectin based, and chitosan based are used in food products. However, edible coatings sometimes provide unpleasant flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…These matrices have included starch, chitosan, sodium alginate, hydroxypropyl methylcellulose, and carnauba wax ( 260 ). As EOs are emulsified, they have been found to have higher stability and lower influence on food sensory qualities, and reduced interaction with other food matrix ingredients, while delivering enhanced biological activity due to the increased surface area and small droplet size ( 261 ). It was also demonstrated that for a film-forming formulation the addition of lemongrass EO emulsions by emulsification with two emulsifiers (Tween 80/pectin) to glycerol-plasticized cassava starch resulted in both EO and emulsifier phases showing good interaction and compatibility.…”
Section: Essential Oil Formulations and Applications In The Food Industrymentioning
confidence: 99%
“…These matrices have included starch, chitosan, sodium alginate, hydroxypropyl methylcellulose, and carnauba wax ( 260 ). As EOs are emulsified, they have been found to have higher stability and lower influence on food sensory qualities, and reduced interaction with other food matrix ingredients, while delivering enhanced biological activity due to the increased surface area and small droplet size ( 261 ). It was also demonstrated that for a film-forming formulation the addition of lemongrass EO emulsions by emulsification with two emulsifiers (Tween 80/pectin) to glycerol-plasticized cassava starch resulted in both EO and emulsifier phases showing good interaction and compatibility.…”
Section: Essential Oil Formulations and Applications In The Food Industrymentioning
confidence: 99%
“…Emulsifiers such as proteins, phospholipids, and polysaccharides are used to maintain the stability of the essential oil emulsion. In addition, surfactants such as sugar esters and polyoxyethylene are also used to reduce the interfacial tension of the emulsion solution by electrostatic/steric stabilisation [112]. This technique has been successfully proven to maintain the efficacy of the essential oil over harsh environmental conditions such as high temperature and provide the slow-release rate of the essential oil [113][114][115].…”
Section: Emulsificationmentioning
confidence: 99%
“…However, the downside is that the strong scents from essential oils could interfere with the true aroma of the produce. This is generally mitigated by the nanoemulsion technique with sodium alginate or pectin-based edible coating and the high-pressure homogenisation technique [112]. All in all, several considerations should be taken into account when applying the essential oil in agricultural productions, such as its volatilisation nature [129] and the activity losses due to the exposure to ultraviolet light, temperature, humidity, and oxygen [130].…”
Section: Nanoprecipitationmentioning
confidence: 99%
“…One of the main features can be in the form of antimicrobial nanoemulsions, for example, nanoemulsions based on plant essential oils, which are associated with biopolymers such as alginate, chitosan, and starch, among others. It has been shown that when essential oils are encapsulated in nanoemulsions, they have less impact on the sensory properties of the food, masking the taste or smell of the core material (coating), yet providing better biological activity of essential oils due to the increase in the surface area [67]. In this way, it is possible to use low doses of bioactive material, increasing the transport of active ingredients through biological membranes, thus intensifying the bioavailability of bioactive compounds, in addition to less interaction with other components of the food matrix.…”
Section: Coatings Based On Essential Oil Nanoemulsionsmentioning
confidence: 99%